Using mathematical induction for integers n >= 1, prove a + (a+d) +...+ (a+nd) = 1/2 (n+1)(2a+nd)?
1 Answer
Dec 11, 2016
Claim:
Proof (by induction):
Base case:
If
Inductive hypothesis:
Suppose that the claim holds true for some integer
Induction step:
We wish to show that the claim holds for
=a+(k+1)d + ((k+1)(2a+kd))/2
(by the inductive hypothesis)
=(2a+2(k+1)d)/2+((k+1)(2a+kd))/2
=(2a+2(k+1)d+(k+1)(2a+kd))/2
=(2a+2(k+1)d+2(k+1)a+k(k+1)d)/2
=(2(k+2)a+(k+1)(k+2)d)/2
=((k+2)(2a+(k+1)d))/2
=(((k+1)+1)(2a+(k+1)d))/2
as desired.
We have supposed the claim is true for
∎